The stuff of dreams : fantasy, anxiety, and psychoanalysis - Hall, Kirsty (Karnac, 2007)
Annotation This book offers a new approach to the problem of anxiety. It suggests that our fantasies offer the key to understanding our anxieties-and vice versa. The principle sources for understanding the phenomenon of fantasy combined with anxiety are drawn from the worlds of psychoanalysis, literature and popular culture. At times, the book offers clinical examples of fantasy/anxiety interactions; at others, literary or popular cultural sources are preferred. The variety of references reflects the chimerical nature of both fantasy and anxiety. The aim throughout is to make technical psychoanalytic ideas easily accessible to the general reader. The balance between clinical ideas, philosophical ideas and literary sources keeps both potential audiences interested. Clinicians may find the idea of thinking dialectically helpful with their patients. Although this approach is implied in both Freud and Lacan, this is the first book to put dialectics center stage in terms of understanding the patient's discourse.